A modified composite catalyst for piperazine synthesis and preparation method thereof
By electrodeposition and hydrothermal treatment of Cu/SiO2 composite catalyst, a Ni/Zr-doped Cu-based catalyst was formed, which solved the problems of difficult separation and poor thermal stability of piperazine catalysts and achieved efficient and selective piperazine synthesis.
Patent Information
- Application Number
- CN202511008722.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-22
- Publication Date
- 2025-09-30
- Estimated Expiration
- 2045-07-22
AI Technical Summary
Existing piperazine catalysts have problems such as difficulty in separation, poor thermal stability and high recycling costs, and free amines are prone to corrosion or side reactions.
A Cu/SiO2 composite catalyst is used to form a Ni/Zr-doped composite Cu-based catalyst through electrodeposition and hydrothermal reaction. Diphosphonic acid compounds are used to react with nickel salts and zirconium salts to form metal phosphonates, thereby improving the dispersibility and active sites of the catalyst and enhancing the rate and selectivity of the catalytic reaction.
The catalytic efficiency, selectivity and cycle durability are improved, the problems of catalyst agglomeration and poor thermal stability are avoided, and efficient piperazine synthesis is achieved.
Smart Images

Figure CN120515453B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a modified composite catalyst for piperazine synthesis and a preparation method thereof. Background Art
[0002] The piperazine molecule contains two cis-type secondary amine nitrogen atoms, providing strong Lewis base sites and excellent nucleophilicity. It can synergistically activate a variety of substrates through coordination, hydrogen bonding, or quaternization. Its applications range from industrial acid gas degassing absorbents to fine chemical coupling reactions. Traditional homogeneous piperazine catalysts offer high activity but face bottlenecks such as difficult separation, poor thermal stability, and high recycling costs. Furthermore, free amines can easily migrate downstream with the product, causing corrosion or side reactions.
[0003] The mainstream synthetic routes of N-alkylpiperazine compounds generally include the following: nucleophilic substitution method, in which piperazine-N nucleophile replaces alkyl halide or dimethyl / diethyl carbonate and other activated alkyl sources to form HX or CO2+ROH products. The catalytic systems used include solid base system and phase transfer catalyst system; "borrowing hydrogen" / dehydrogenation coupling method, in which alcohol is first dehydrogenated to aldehyde / ketone by metal, and the intermediate imine is condensed and then "returned" the hydrogen atom to obtain N-alkylamine. The main by-products are primary or secondary alcohol compounds. The catalytic systems used include Ru-, Ir-, Mn-, Co-PNP / PNN pincer complexes and Ni, Cu, Pd, Ag and other loaded nanometals or metal / acid bifunctional composite catalysts; the reductive amination method is to first condense aldehyde / ketone with piperazine to form imine, and then hydrogenate it under hydrogen or methanol hydrogen in situ conditions to generate N-alkylamine, with water as the main by-product. The catalytic systems used include RaneyNi and its alloys, Pd / C, Pt / C and other high-pressure hydrogenation catalysts.
[0004] Common catalyst systems include the following: Raney nickel and Ni-based heterogeneous catalysts. Raney nickel is a common industrial hydrogenation catalyst. It is composed of a Ni-Al alloy with alkali leaching to remove Al to form a porous Ni skeleton with a high specific surface area. This material exhibits high activity in the reductive amination of piperazine, but suffers from technical drawbacks such as easy sintering, sulfur sensitivity, and difficulty in selectively controlling monoalkylation. Major optimization directions in recent years include metal doping: by simultaneously introducing Mo or Cu into the Ni matrix, excessive hydrogenation of the Ni surface can be suppressed, improving the adsorption and conversion efficiency of imine intermediates; Mo doping also enhances resistance to sulfur poisoning. Simultaneously, loading on high-surface-area SiO2, Al2O3, or carbon materials significantly improves dispersion and reduces agglomeration, while also enabling selectivity to be manipulated by leveraging the acid-base properties of the support surface. A core-shell structure: Ni particles are coated with a sintering-resistant carbon shell (Ni@C), forming a physical barrier that prevents agglomeration and controls substrate diffusion through the shell pores, achieving higher catalytic stability and recyclability. Precious metal dispersed catalysts such as Pd / C and Pt / C, and Pd and Pt nanoparticles supported on supports such as activated carbon or alumina, are typical heterogeneous hydrogenation catalysts suitable for the reductive amination and "borrowing hydrogen" coupling pathways of piperazine. Their advantages lie in high dispersion and wide substrate applicability, but they also face cost and recovery challenges. Key improvement strategies include: Bifunctional composites: Co-loading Pd / C with acidic solids (such as H-β zeolite and SO3H-SBA-15) to achieve synergistic catalysis of dehydrogenation and imine condensation, which can effectively reduce over-alkylation side reactions and improve monoalkylation selectivity; Fine particle size control: By controlling the reduction conditions or introducing surface modifiers, the metal particles are uniformly distributed in the range of 2-5 nm, which not only enhances the exposure of active centers but also reduces metal usage and costs; Support modification: Introducing nitrogen / sulfur functional groups on the support surface enhances electronic interactions at the metal-support interface, thereby improving the catalyst's sintering resistance and anti-poisoning properties. Pincer complex catalysts (Ru-, Ir-, Mn-, Co-PNP / PNN) enable highly controllable dehydrogenation / back-hydrogenation catalytic cycles through multiple chelations between the metal center and a macrocyclic ligand. Typical examples include Ru-MACHO-BH and [RuHCl(CO)(PNP)]. This type of homogeneous catalyst exhibits excellent activity and specificity in "borrowing hydrogen" coupling reactions at loadings as low as 0.5-2 mol%. Current optimization directions include: Ligand modification: By introducing sulfonic acid groups at the alkylene or aryl positions of the PNP ligand, the catalyst becomes water-soluble, facilitating its application in hydrophilic substrate systems and enabling catalyst recovery and regeneration via phase separation; Non-precious metal substitution: The development of a series of Mn and Co-PNP / PNN catalysts not only significantly reduces cost but also achieves highly efficient N-alkylation under mild conditions (<110°C, without the addition of H2).MOF and acidic mesoporous silica composite catalytic system, metal-organic framework (MOF) and silicon-based mesoporous materials (such as SBA-15, MCM-41) are widely used in metal / acid bifunctional catalysis due to their adjustable pores and rich functionalization sites. Summary of the Invention
[0005] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a modified composite catalyst for the synthesis of piperazines and a preparation method thereof. The present invention uses Cu as the main element of the catalyst, and co-deposits Cu and SiO2 on a negative electrode titanium plate by electrodeposition to obtain Cu / SiO2. SiO2 is used as a carrier to improve the dispersion of Cu and avoid agglomeration to reduce the active sites of Cu. At the same time, a metal phosphonate is formed by a diphosphonic acid compound with a nickel salt and a zirconium salt. After a hydrothermal reaction with the Cu / SiO2 composite material, a Ni / Zr-doped composite Cu-based catalyst is formed after calcination. The catalyst can provide additional Lewis acid sites, thereby improving the rate and efficiency of the catalytic reaction. It has high metal dispersion, strong interface bonding, synergistic multifunctional active sites and excellent thermochemical stability, and can significantly improve the catalytic efficiency, selectivity and cycle durability.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The present invention provides a method for preparing a modified composite catalyst for piperazine synthesis, which specifically comprises the following steps:
[0007] S1. Dissolve siloxane in an anhydrous alcohol solvent, add ammonium chloride compound under an inert gas atmosphere, mix thoroughly, add a catalyst, raise the temperature and stir to react. After the reaction is completed, cool the reaction system to room temperature, remove the reaction solvent, and purify to obtain a cationic modified siloxane;
[0008] S2, dissolving the cationic modified siloxane prepared in step S1 in an ethanol aqueous solution, adding copper sulfate pentahydrate, sulfuric acid, and sodium citrate, mixing well, and ultrasonically treating to obtain an electrolyte;
[0009] S3. Place a copper plate and a titanium plate in the electrolyte prepared in step S2, connect the negative electrode of the power supply to the titanium plate, connect the positive electrode of the power supply to the copper plate, start the DC power supply, and set the current density to 1-5 mA / cm 2 , setting the electrodeposition time to 300-600s, and maintaining the electrodeposition temperature at room temperature. After the electrodeposition is completed, the deposits on the surface of the titanium plate are peeled off by physical methods, and after washing, a Cu / SiO2 composite material is obtained;
[0010] S4, dissolving the diphosphonic acid compound in deionized water, adding a NaOH aqueous solution, mixing well, adding an auxiliary agent, adding a metal salt, stirring overnight at room temperature, raising the reaction temperature to 150-170° C., and continuing the reaction for 30-48 hours. After the reaction is completed, cooling, filtering and collecting the solid, washing, and drying to obtain a metal phosphonate;
[0011] S5. Dissolving the metal phosphonate prepared in step S4 in an ethanol aqueous solution, adding the Cu / SiO2 composite material prepared in step S3 and dispersing it in the reaction system, continuously stirring, adding sodium citrate, adjusting the reaction pH to 8-9, continuously stirring at room temperature for 2-3 hours, transferring to a high-pressure reactor for hydrothermal reaction, cooling to room temperature, filtering to remove solids, washing with deionized water and anhydrous ethanol, and vacuum drying to obtain a catalyst precursor;
[0012] S6. The catalyst precursor prepared in step S5 is placed in a reactor and calcined. In an air atmosphere, the temperature is raised to 450-550° C., kept warm for 3-4 hours, and then a H2 / N2 mixed gas is introduced, maintained at 400-450° C., calcined for 2-3 hours, and cooled to obtain a modified composite catalyst.
[0013] Preferably, in step S1, the silicon hydrogen siloxane includes any one of trimethoxysilane, triethoxysilane, tris(trimethylsiloxy)silane, and triisopropoxysilane;
[0014] Preferably, in step S1, the ammonium chloride compound includes at least one of allyltrimethylammonium chloride, diallyldimethylammonium chloride, and tetraallylammonium chloride;
[0015] Preferably, in step S1, the catalyst comprises at least one of a platinum / carbon catalyst and a palladium / carbon catalyst, and the added mass of the catalyst is 0.05%-0.1% of the mass of the silicon hydrogen siloxane;
[0016] Preferably, in step S1, the stirring reaction temperature is 40-60°C, the stirring reaction speed is 200-400 rpm, and the stirring reaction time is 4-8 hours;
[0017] Preferably, in step S2, the mass concentration of the cationic modified siloxane in the ethanol aqueous solution is 0.2-0.4 g / L;
[0018] Preferably, in step S2, the mass concentration of the copper sulfate pentahydrate in the ethanol aqueous solution is 40-50 g / L;
[0019] Preferably, in step S2, the mass concentration of sulfuric acid in the ethanol aqueous solution is 10-20 g / L;
[0020] Preferably, in step S2, the mass concentration of sodium citrate is 5-10 g / L;
[0021] Preferably, in step S4, the diphosphonic acid compound includes at least one of o-xylene diphosphonic acid, 1,4-butanediphosphonic acid, 1,2-vinyl diphosphonic acid, 1,4-benzenediphosphonic acid, p-phenylene diphosphonic acid, and 4,4'-biphenyl diphosphonic acid;
[0022] Preferably, in step S4, the auxiliary agent includes at least one of 1,10-phenanthroline, 2,2'-bipyridine, 4,4'-bipyridine, 5-nitro-1,10-phenanthroline, and 2,9-dimethyl-1,10-phenanthroline;
[0023] Preferably, in step S4, the metal salt includes at least one of a nickel salt and a zirconium salt;
[0024] Preferably, in step S4, the mass ratio between the diphosphonic acid compound and the metal salt is 1:0.5-1.5;
[0025] Preferably, in step S4, the mass ratio between the nickel salt and the zirconium salt in the metal salt is 3-7:2-5;
[0026] Preferably, in step S4, the concentration of NaOH in the NaOH aqueous solution is 1 mol / L, and the volume fraction of the NaOH aqueous solution in deionized water is 4%-6%;
[0027] Preferably, in step S4, the mass ratio between the diphosphonic acid compound and the adjuvant is 1:2-2.4;
[0028] Preferably, in step S5, the mass concentration of the metal phosphonate in the ethanol aqueous solution is 3-5 mg / mL;
[0029] Preferably, in step S5, the mass concentration of the Cu / SiO2 composite material in the ethanol aqueous solution is 60-80 mg / mL;
[0030] Preferably, in step S5, the mass concentration of the sodium citrate in the ethanol aqueous solution is 2-4 mg / mL;
[0031] Preferably, in step S5, the reaction temperature of the hydrothermal reaction is 160-180° C., and the hydrothermal reaction time is 12-18 hours.
[0032] The present invention also provides a modified composite catalyst for piperazine synthesis prepared according to the above preparation method;
[0033] Preferably, the modified composite catalyst is used to catalyze the synthesis of N-alkylpiperazine;
[0034] Preferably, the modified composite catalyst is used to catalyze the synthesis of 1,4-dimethylpiperazine from N-methyldiethanolamine and monomethylamine.
[0035] The beneficial effects achieved by the present invention are as follows:
[0036] The invention provides a modified composite catalyst for piperazine synthesis and a preparation method thereof. The invention uses Cu as a main element of the catalyst, and co-deposits Cu and SiO2 on a negative electrode titanium plate by electrodeposition to obtain Cu / SiO2. SiO2 is used as a carrier to improve the dispersibility of Cu and avoid agglomeration that causes a reduction in Cu active sites. At the same time, a diphosphonic acid compound is reacted with a nickel salt and a zirconium salt to form a metal phosphonate, which undergoes a hydrothermal reaction with the Cu / SiO2 composite material and is then calcined to form a Ni / Zr-doped composite Cu-based catalyst, which can provide additional Lewis sites, thereby improving the rate and efficiency of the catalytic reaction. In the invention, silicon hydrogen siloxane is used as a raw material, and the Si-H group in its structure has reaction activity. After reacting with ammonium chloride containing an allyl group, a quaternary ammonium salt cationic group can be introduced into the siloxane. During the electroplating process, an electrolyte containing copper sulfate pentahydrate and cationic modified siloxane as main components is used. During the electroplating process, as current is applied, Cu adsorbed on the surface of the SiO2 is released. 2+ Reduced to Cu 0 The carrier-metal interface is firmly bonded and not easy to grow into large-sized agglomerates. Some SiO2 particles that are not completely deposited will also be mechanically wrapped into the metal deposition layer, further locking the small-sized Cu nanoparticles inside the composite material, further improving the dispersion of Cu on the SiO2 carrier. The nano / micron-scale dispersed Cu particles have a higher specific surface area, which increases the active sites and is beneficial to the adsorption and activation of reactant molecules on the catalyst surface, thereby improving the overall catalytic rate. The highly dispersed metal-carrier composite structure is usually accompanied by a mesoporous or microporous network, which can provide a good reactant-product diffusion channel. The reactants are more easily exposed to the internal active sites, and the products can also quickly desorb and leave, reducing diffusion. Resistance, improve catalytic efficiency; in the present invention, the chelating ability of the diphosphonic acid compound for metal ions is enhanced under alkaline conditions. At the same time, due to the addition of the auxiliary agent, its electron donor property can adjust the electron density of the metal center, affecting the subsequent coordination polymerization rate and product crystal form. Nickel nitrate hexahydrate and zirconium oxychloride octahydrate are added successively. The two metal ions play a coordination and bridging role in the alkaline phosphonate / auxiliary agent mixture at the same time. The phosphonate has multiple tooth sites and can bridge multiple metal centers at the same time, promoting a binary or multi-metal-phosphonate network structure. The diphosphonic acid compound contains two -PO3H2 groups, which can generate -PO3H- or -PO3 after partial deprotonation by NaOH. 2- , with single tooth, double tooth or multi-bridge mode and Zr 4+ / Ni 2+ Coordination, the remaining negative charge is not compensated by the metal ions, thus retaining anionic sites in the molecular structure skeleton. Through electrostatic interaction with the cations in the Cu / SiO2 composite material, a uniform adhesion layer is formed on the surface of the Cu / SiO2 composite material. Ni / Zr can improve catalytic activity by increasing Lewis acid sites. After calcination, the multi-level structure forms a relatively open pore network, which is conducive to the rapid entry and exit of reactants / products; the close contact between the metal phosphonate and the Cu phase constructs an efficient electron conduction path, promoting electron exchange at the surface active sites. The modified composite catalyst described in the present invention has high metal dispersion, strong interface bonding, synergistic multifunctional active sites and excellent thermochemical stability, which can significantly improve catalytic efficiency, selectivity and cycle durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is an SEM image of the modified composite catalyst prepared in Example 1 of the present invention;
[0038] Figure 2 The performance results of the modified composite catalysts prepared in Examples 1-3 and Comparative Examples 1-3 of the present invention are shown;
[0039] Figure 3 This is a graph showing the stability performance results of the modified composite catalysts prepared in Examples 1-3 of the present invention and Comparative Examples 1-3.
[0040] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those familiar to those skilled in the art. Furthermore, any methods and materials similar or equivalent to those described herein can be applied to the present invention. The preferred embodiments and materials described herein are for illustrative purposes only and are not intended to limit the scope of this application.
[0043] The experimental methods in the following examples, unless otherwise specified, are conventional methods; the test materials and test strains used in the following examples, unless otherwise specified, are purchased from commercial channels.
[0044] Example 1
[0045] This embodiment provides a method for preparing a modified composite catalyst for piperazine synthesis, which specifically comprises the following steps:
[0046] S1. Take 2.0 mL of triethoxysilane and place it in a flask. Prepare an anhydrous alcohol solvent by mixing anhydrous ethanol and anhydrous isopropanol in a volume ratio of 1:1. Add 10 mL of anhydrous alcohol solvent to the flask and stir at 200 rpm until the triethoxysilane is fully dissolved. Then, introduce flowing nitrogen and add 1.5 mL of diallyldimethylammonium chloride (commercially available is generally an aqueous solution of diallyldimethylammonium chloride with a concentration of 60 wt %). Continue mixing until the reactants are completely dissolved. Add 18 mg of platinum / carbon catalyst and raise the reaction temperature to 40°C. Continue stirring for 6 hours. The reaction is terminated. After the reaction is cooled to room temperature, the reaction solvent is removed by vacuum distillation and purified by column chromatography to obtain a cationic modified siloxane.
[0047] S2, take 20mg of the cationic modified siloxane prepared in step S1 and place it in a flask, add ethanol aqueous solution (V 乙醇 :V 水 =1:1) 50 mL, raise the temperature to 45 ° C, stir at 600 rpm until the cationic modified siloxane is fully dissolved, add 2 g of copper sulfate pentahydrate and 0.5 g of sodium citrate, add sulfuric acid at a mass concentration of 10 g / L, continue stirring for 30 minutes, and transfer to ultrasonic treatment at 500 W power for 2 hours to obtain an electrolyte;
[0048] S3. Place a copper plate and a titanium plate in the electrolyte prepared in step S2, connect the copper plate as the positive electrode to the positive electrode of the power supply, and connect the titanium plate as the negative electrode to the negative electrode of the power supply. Stick insulating tape on the back of the copper plate and the titanium plate, start the DC power supply, and adjust the current density to 2 mA / cm 2 The electrodeposition time was set to 300s, and the electrodeposition temperature was kept at room temperature. After each deposition, the deposits on the titanium plate were peeled off, washed repeatedly with deionized water and anhydrous ethanol, and dried in vacuum at 40°C for 12h to obtain a Cu / SiO2 composite material.
[0049] S4. Take 50 mg of 4,4'-biphenyldiphosphonic acid and place it in a reactor. Add 10 mL of deionized water and mix well. Then add 0.4 mL of 1 mol / L NaOH aqueous solution and stir at 300 rpm. After stirring for 1 hour, add 0.1 g of 5-nitro-1,10-phenanthroline as an auxiliary agent. Continue mixing for 10 minutes. Then add 35 mg of nickel nitrate hexahydrate and 15 mg of zirconium oxychloride octahydrate. After stirring and reacting overnight, increase the reaction temperature to 160°C and react for 48 hours. After the reaction is completed, cool naturally to room temperature, collect the solid, wash it repeatedly with deionized water to remove unreacted compounds, and then vacuum dry it at 30°C for 12 hours to obtain a metal phosphonate.
[0050] S5, take 30mg of the metal phosphonate prepared in step S4 and place it in a reactor, add ethanol aqueous solution (V 乙醇 / V 水 = 20%), after uniformly dispersing the metal phosphonate, add 0.6 g of the Cu / SiO2 composite material prepared in step S3, stir at 500 rpm until the reaction system is uniformly dispersed, add 20 mg of sodium citrate, and dropwise add 1 mol / L ammonia solution to adjust the pH of the reaction system to 8.5. After continuing stirring for 30 minutes, transfer the reaction system to an autoclave, increase the reaction temperature to 180°C, and react for 12 hours. The reaction is completed. After the reaction is cooled to room temperature, the solid is collected by filtration, repeatedly washed with anhydrous ethanol and deionized water until neutral, and then dried in vacuo at 80°C for 4 hours to obtain a catalyst precursor;
[0051] S6, placing the catalyst precursor prepared in step S5 in a reactor and calcining it, raising the temperature to 450° C. in an air atmosphere, keeping it warm for 3 hours, introducing a H2 / N2 mixed gas with a H2 volume fraction of 10%, maintaining the temperature at 400° C., calcining it for 3 hours, and cooling it to obtain a modified composite catalyst;
[0052] The modified composite catalyst prepared in Example 1 of the present invention was observed by electron microscopy using a Zeiss high-resolution scanning electron microscope at a field voltage of 20 kV. Figure 1 This is the SEM image of the modified composite catalyst prepared in Example 1 of the present invention.
[0053] This embodiment also provides a modified composite catalyst for piperazine synthesis prepared according to the above preparation method.
[0054] Example 2
[0055] This embodiment provides a method for preparing a modified composite catalyst for piperazine synthesis, which specifically comprises the following steps:
[0056] S1. Take 1.5 mL of trimethoxysilane and place it in a flask. Prepare an anhydrous alcohol solvent by mixing anhydrous ethanol and anhydrous isopropanol in a volume ratio of 1:1. Add 10 mL of anhydrous alcohol solvent to the flask and stir at 200 rpm until the triethoxysilane is fully dissolved. Then, introduce flowing nitrogen and add 1.63 g of allyltrimethylammonium chloride. Continue mixing until the reactants are completely dissolved. Add 12 mg of palladium / carbon catalyst and raise the reaction temperature to 50°C. After stirring for 4 hours, the reaction is terminated. The reaction mixture is cooled to room temperature and the reaction solvent is removed by vacuum distillation. After purification by column chromatography, a cationic modified siloxane is obtained.
[0057] S2, take 24 mg of the cationic modified siloxane prepared in step S1 and place it in a flask, add ethanol aqueous solution (V 乙醇 :V 水 =1:1) 80 mL, raise the temperature to 45 ° C, stir at 600 rpm until the cationic modified siloxane is fully dissolved, add 4 g of copper sulfate pentahydrate and 0.4 g of sodium citrate, add sulfuric acid at a mass concentration of 15 g / L, continue stirring for 30 minutes, and transfer to ultrasonic treatment at 500 W power for 2 hours to obtain an electrolyte;
[0058] S3. Place a copper plate and a titanium plate in the electrolyte prepared in step S2, use the copper plate as the positive electrode and connect it to the positive electrode of the power supply, use the titanium plate as the negative electrode and connect it to the negative electrode of the power supply, apply insulating tape to the back of the copper plate and the titanium plate, start the DC power supply, and adjust the current density to 1 mA / cm 2 The electrodeposition time was set to 450s, and the electrodeposition temperature was kept at room temperature. After each deposition three times, the deposits on the titanium plate were peeled off, washed repeatedly with deionized water and anhydrous ethanol, and dried in vacuum at 40°C for 12h to obtain the Cu / SiO2 composite material.
[0059] S4. 0.1 g of p-phenylenediphosphonic acid was placed in a reactor, 10 mL of deionized water was added and mixed evenly, 0.5 mL of a 1 mol / L NaOH aqueous solution was added, and the mixture was stirred at 300 rpm for 1 h. Then, 0.22 g of an auxiliary agent, 1,10-phenanthroline, was added, and the mixture was mixed for 10 min. Then, 25 mg of nickel nitrate hexahydrate and 25 mg of zirconium oxychloride octahydrate were added. The mixture was stirred and reacted overnight. The reaction temperature was raised to 150 ° C. and the reaction was allowed to proceed for 40 h. After the reaction was terminated, the mixture was naturally cooled to room temperature, the solid was collected, washed repeatedly with deionized water to remove unreacted compounds, and then dried in vacuo at 30 ° C. for 12 h to obtain a metal phosphonate.
[0060] S5, take 50 mg of the metal phosphonate prepared in step S4 and place it in a reactor, add ethanol aqueous solution (V 乙醇 / V 水= 20%), after uniformly dispersing the metal phosphonate, add 0.8 g of the Cu / SiO2 composite material prepared in step S3, stir at 500 rpm until the reaction system is uniformly dispersed, add 40 mg of sodium citrate, and dropwise add 1 mol / L ammonia solution to adjust the pH of the reaction system to 9.0. After continuing stirring for 30 minutes, transfer the reaction system to an autoclave, increase the reaction temperature to 160°C, and react for 15 hours. The reaction is completed. After the reaction is cooled to room temperature, the solid is collected by filtration, repeatedly washed with anhydrous ethanol and deionized water until neutral, and then dried in vacuo at 80°C for 4 hours to obtain a catalyst precursor;
[0061] S6. The catalyst precursor prepared in step S5 is placed in a reactor for calcination. The temperature is raised to 500° C. in an air atmosphere. After being kept warm for 2 h, a H2 / N2 mixed gas is introduced with a H2 volume fraction of 10% at 450° C. The mixture is calcined for 2 h and then cooled to obtain a modified composite catalyst.
[0062] This embodiment also provides a modified composite catalyst for piperazine synthesis prepared according to the above preparation method.
[0063] Example 3
[0064] This embodiment provides a method for preparing a modified composite catalyst for piperazine synthesis, which specifically comprises the following steps:
[0065] S1. Take 3.0 mL of triethoxysilane and place it in a flask. Prepare an anhydrous alcohol solvent by mixing anhydrous ethanol and anhydrous isopropanol in a volume ratio of 1:1. Add 10 mL of anhydrous alcohol solvent to the flask and stir at 200 rpm until the triethoxysilane is fully dissolved. Then, introduce flowing nitrogen and add 2.67 g of tetraallyl ammonium chloride. Continue mixing until the reactants are completely dissolved. Add 13 mg of platinum / carbon catalyst and increase the reaction temperature to 60°C. After stirring for 8 hours, the reaction is terminated. The reaction mixture is cooled to room temperature and the reaction solvent is removed by vacuum distillation. After purification by column chromatography, a cationic modified siloxane is obtained.
[0066] S2, take 20mg of the cationic modified siloxane prepared in step S1 and place it in a flask, add ethanol aqueous solution (V 乙醇 :V 水 =1:1) 100 mL, raise the temperature to 45°C, stir at 600 rpm until the cationic modified siloxane is fully dissolved, add 4.5 g of copper sulfate pentahydrate and 0.8 g of sodium citrate, add sulfuric acid at a mass concentration of 20 g / L, continue stirring for 30 min, and transfer to ultrasonic treatment at 500 W power for 2 h to obtain an electrolyte;
[0067] S3. Place a copper plate and a titanium plate in the electrolyte prepared in step S2, use the copper plate as the positive electrode and connect it to the positive electrode of the power supply, use the titanium plate as the negative electrode and connect it to the negative electrode of the power supply, apply insulating tape to the back of the copper plate and the titanium plate, start the DC power supply, and adjust the current density to 5 mA / cm 2 The electrodeposition time was set to 600s, and the electrodeposition temperature was kept at room temperature. After each deposition, the deposits on the titanium plate were peeled off, washed repeatedly with deionized water and anhydrous ethanol, and dried in vacuum at 40°C for 12h to obtain a Cu / SiO2 composite material.
[0068] S4. 0.1 g of 1,2-vinyldiphosphonic acid was placed in a reactor, 10 mL of deionized water was added and mixed evenly, 0.6 mL of a 1 mol / L NaOH aqueous solution was added, and the mixture was stirred at 300 rpm. After stirring for 1 h, 0.24 g of an auxiliary agent 2,2'-bipyridine was added, and the mixture was mixed for 10 min. Then, 0.1 g of nickel nitrate hexahydrate and 50 mg of zirconium oxychloride octahydrate were added. The mixture was stirred and reacted overnight, and the reaction temperature was raised to 170 ° C. and the reaction was allowed to proceed for 30 h. After the reaction was terminated, the mixture was naturally cooled to room temperature, the solid was collected, and the unreacted compounds were removed by repeated washing with deionized water. The solid was then dried at 30 ° C. under vacuum for 12 h to obtain a metal phosphonate.
[0069] S5, take 40 mg of the metal phosphonate prepared in step S4 and place it in a reactor, add ethanol aqueous solution (V 乙醇 / V 水 = 20%), after uniformly dispersing the metal phosphonate, 0.7 g of the Cu / SiO2 composite material prepared in step S3 was added, and the mixture was stirred at 500 rpm until the reaction system was uniformly dispersed. 50 mg of sodium citrate was added, and 1 mol / L ammonia solution was added dropwise to adjust the pH of the reaction system to 8.0. After continuing to stir for 30 min, the reaction system was transferred to a high-pressure reactor, the reaction temperature was increased to 170°C, and the reaction was completed after 18 h. After the reaction was cooled to room temperature, the solid was collected by filtration, repeatedly washed with anhydrous ethanol and deionized water until neutral, and then dried in vacuo at 80°C for 4 h to obtain a catalyst precursor;
[0070] S6. The catalyst precursor prepared in step S5 is placed in a reactor for calcination. The temperature is raised to 550° C. in an air atmosphere. After being kept warm for 2 h, a H2 / N2 mixed gas is introduced with a H2 volume fraction of 10% at 400° C. The mixture is calcined for 3 h and then cooled to obtain a modified composite catalyst.
[0071] This embodiment also provides a modified composite catalyst for piperazine synthesis prepared according to the above preparation method.
[0072] Comparative Example 1
[0073] This comparative example provides a modified composite catalyst and a preparation method thereof, which differs from Example 1 only in that the preparation method of the modified composite catalyst does not include step S1, the cationic modified siloxane in step S2 is replaced by ethyl orthosilicate of the same concentration, and the remaining components and component contents are the same as those in Example 1.
[0074] Comparative Example 2
[0075] This comparative example provides a modified composite catalyst and a preparation method thereof. The difference between the modified composite catalyst and Example 1 is that the preparation method of the modified composite catalyst does not include step S4, and step S5 is modified as follows: 35 mg of nickel nitrate hexahydrate and 13 mg of zirconium oxychloride octahydrate are placed in a reactor, and an ethanol aqueous solution (V 乙醇 / V 水 = 20%) 10 mL, after mixing evenly, 0.6 g of the Cu / SiO2 composite material prepared in step S3 was added, and the mixture was stirred at 500 rpm until the reaction system was evenly dispersed. 20 mg of sodium citrate was added, and 1 mol / L ammonia solution was added dropwise to adjust the pH of the reaction system to 8.5. After continuing to stir for 30 min, the reaction was transferred to a high-pressure reactor, the reaction temperature was increased to 180 ° C, and the reaction was completed after 12 h. After the reaction was cooled to room temperature, the solid was collected by filtration, repeatedly washed with anhydrous ethanol and deionized water until neutral, and then dried in vacuo at 80 ° C for 4 h to obtain a catalyst precursor. The remaining components and component contents were the same as those in Example 1.
[0076] Comparative Example 3
[0077] This comparative example provides a modified composite catalyst and a preparation method thereof, which differs from Example 1 only in that the preparation method of the modified composite catalyst does not include steps S4 and S5, and the remaining components and component contents are the same as those in Example 1.
[0078] Application Examples
[0079] The modified composite catalyst for piperazine synthesis prepared by the present invention is specifically used for the synthesis of N-alkylpiperazine. The following is the synthesis route of 1,4-dimethylpiperazine:
[0080] ;
[0081] The synthesis method of 1,4-dimethylpiperazine comprises the following steps: accurately measuring two liquid raw materials according to a molar ratio of N-methyldiethanolamine (MDEA): monomethylamine (MMA) = 1:2.05, and ensuring that the molar ratio of dry and deoxygenated high-purity hydrogen to MDEA is 6:1, the liquid raw materials are pumped into a shell and tube evaporator, heated to 180°C and completely vaporized, and then merged with hydrogen preheated to 200°C and 3.6MPa to form a homogeneous gas flow that enters a 316L stainless steel tubular fixed bed reactor, the reactor is filled with the modified composite catalyst prepared in Examples 1-3 of the present invention and Comparative Examples 1-3, and is filled to 2 / 3 of the total height of the tubular fixed bed reactor; at 260°C, 3.5MPa and a liquid hourly space velocity of 3h -1 Under the following conditions, MMA first dehydrates MDEA to form dimethylaminoethanol by amination, and the intermediate then continues to dehydrate and close the ring on the catalyst surface and is stabilized by hydrogenation, converting MDEA into 1,4-dimethylpiperazine (DMPZ) in a single pass. The reaction products are quantitatively analyzed, and the conversion and selectivity of the modified composite catalysts prepared in Examples 1-3 of the present invention and Comparative Examples 1-3 are calculated using N-methyldiethanolamine as the limiting reactant;
[0082] ;
[0083] ;
[0084] is the added molar mass of the MDEA as a reactant, unit: mol; is the remaining molar mass after the MDEA reaction is completed, unit: mol; is the molar mass of the DMPZ obtained as the DMPZ reaction product, in mol;
[0085] Figure 2 The performance results of the modified composite catalysts prepared in Examples 1-3 of the present invention and Comparative Examples 1-3 are shown in the figure. As shown in the figure, the conversion rate and selectivity of the modified composite catalysts prepared in Examples 1-3 are both high, basically maintained at above 95%, indicating that the catalytic activity of the catalysts prepared in Examples 1-3 of the present invention is high. At the same time, the orientation of the target product 1,4-dimethylpiperazine is high, and it can adsorb Cu in the electrodeposition process. 2+The complex anion formed by coordination improves the uniformity of Cu dispersion on the SiO2 carrier. At the same time, since the cationic group on its surface is active, it can be evenly deposited on the SiO2 surface in the hydrothermal reaction with the metal phosphonate to avoid agglomeration, thereby having more active sites. The modified composite catalyst prepared in Comparative Example 1 replaces the siloxane with cationic ethyl orthosilicate during the preparation process. This is consistent with the high conversion rate and low selectivity shown by the modified composite catalyst prepared in Comparative Example 1, resulting in a decrease in hydrogen activation efficiency and anti-water toxicity, and a slightly lower selectivity. In the modified composite material prepared in Comparative Example 2, Ni / Zr is deposited in the form of oxygen (hydrogen) compounds, with a strong acidity and uneven distribution. It is easy to promote MMA self-condensation and MDEA excessive dehydrogenation, and the Lewis acid / base position is unbalanced, resulting in an increase in secondary polycondensation. The modified composite catalyst described in Comparative Example 3 is equivalent to a single Cu / cationic SiO2 catalyst, which can only complete hydrogenation when the intermediate has been generated, lacks selective dehydration-ring closure activity, and has the defects of low conversion rate, poor selectivity, and many by-products.
[0086] Figure 3 The stability performance results of the modified composite catalysts prepared in Examples 1-3 of the present invention and Comparative Examples 1-3 are shown in the figure. As shown in the figure, the catalytic performance stability of the modified catalytic materials prepared in Examples 1-3 of the present invention is relatively high within 80 hours, and the conversion rate can be maintained at a high level, while the modified composite catalysts prepared in Comparative Examples 1-3 have different degrees of reduction in stability, especially after 30 hours, the decline in stability is particularly obvious.
[0087] While the embodiments of the present invention have been shown and described, it will be apparent to those skilled in the art that various changes, modifications, substitutions, and alterations can be made to the embodiments without departing from the principles and spirit of the invention.
[0088] The present invention and its embodiments are described above. Such description is not restrictive. The drawings show only one embodiment of the present invention, and actual applications are not limited thereto. In short, if a person skilled in the art is inspired by the above, and does not deviate from the purpose of the present invention, any method and embodiment similar to the technical solution without creative design shall fall within the scope of protection of the present invention.
Claims
1. A method for preparing a modified composite catalyst for piperazine synthesis, characterized in that: The specific steps include: S1. Dissolve siloxane in an anhydrous alcohol solvent, add ammonium chloride compound under an inert gas atmosphere, mix thoroughly, add a catalyst, raise the temperature and stir to react. After the reaction is completed, cool the reaction system to room temperature, remove the reaction solvent, and purify to obtain a cationic modified siloxane; S2, dissolving the cationic modified siloxane prepared in step S1 in an ethanol aqueous solution, adding copper sulfate pentahydrate, sulfuric acid, and sodium citrate, mixing well, and ultrasonically treating to obtain an electrolyte; S3. Place a copper plate and a titanium plate in the electrolyte prepared in step S2, connect the negative electrode of the power supply to the titanium plate, connect the positive electrode of the power supply to the copper plate, start the DC power supply, and set the current density to 1-5 mA / cm 2 , setting the electrodeposition time to 300-600s, and maintaining the electrodeposition temperature at room temperature. After the electrodeposition is completed, the deposits on the surface of the titanium plate are peeled off by physical methods, and after washing, a Cu / SiO2 composite material is obtained; S4, dissolving the diphosphonic acid compound in deionized water, adding a NaOH aqueous solution, mixing well, adding an auxiliary agent, adding a metal salt, stirring overnight at room temperature, raising the reaction temperature to 150-170 ° C, and continuing the reaction for 30-48 hours. After the reaction is completed, cooling, filtering and collecting the solid, washing, and drying to obtain a metal phosphonate; the metal salt is a nickel salt and a zirconium salt, and the mass ratio between the nickel salt and the zirconium salt is 3-7:2-5; S5. Dissolve the metal phosphonate prepared in step S4 in an ethanol aqueous solution, add the Cu / SiO2 composite material prepared in step S3 and disperse it in the reaction system, continue stirring, add sodium citrate, adjust the reaction pH to 8-9, continue stirring at room temperature for 2-3 hours, transfer to a high-pressure reactor for hydrothermal reaction, cool to room temperature, filter to remove solids, wash with deionized water and anhydrous ethanol, and vacuum dry to obtain a catalyst precursor; S6. Place the catalyst precursor prepared in step S5 in a reactor and calcine it. In an air atmosphere, raise the temperature to 450-550°C, keep it warm for 3-4 hours, introduce a H2 / N2 mixed gas, maintain the temperature at 400-450°C, calcine it for 2-3 hours, and then cool it to obtain a modified composite catalyst.
2. The method for preparing a modified composite catalyst for piperazine synthesis according to claim 1, wherein: In step S1, the silicon hydrogen siloxane includes any one of trimethoxysilane, triethoxysilane, tris(trimethylsiloxy)silane, and triisopropoxysilane; and the ammonium chloride compound includes at least one of allyltrimethylammonium chloride, diallyldimethylammonium chloride, and tetraallylammonium chloride.
3. The method for preparing a modified composite catalyst for piperazine synthesis according to claim 2, wherein: In step S1, the catalyst includes at least one of a platinum / carbon catalyst and a palladium / carbon catalyst, and the added mass of the catalyst is 0.05%-0.1% of the mass of the silicon hydrogen siloxane; the temperature of the stirring reaction is 40-60°C, the stirring speed of the stirring reaction is 200-400 rpm, and the reaction time of the stirring reaction is 4-8h.
4. The method for preparing a modified composite catalyst for piperazine synthesis according to claim 3, wherein: In step S2, the mass concentration of the cationic modified silicone in the ethanol aqueous solution is 0.2-0.4 g / L; the mass concentration of the copper sulfate pentahydrate in the ethanol aqueous solution is 40-50 g / L; the mass concentration of the sulfuric acid in the ethanol aqueous solution is 10-20 g / L; and the mass concentration of the sodium citrate is 5-10 g / L.
5. The method for preparing a modified composite catalyst for piperazine synthesis according to claim 4, wherein: In step S4, the diphosphonic acid compound includes at least one of o-xylene diphosphonic acid, 1,4-butanediphosphonic acid, 1,2-vinyl diphosphonic acid, 1,4-phenylenediphosphonic acid, p-phenylenediphosphonic acid, and 4,4'-biphenyl diphosphonic acid; and the auxiliary agent includes at least one of 1,10-phenanthroline, 2,2'-bipyridine, 4,4'-bipyridine, 5-nitro-1,10-phenanthroline, and 2,9-dimethyl-1,10-phenanthroline.
6. The method for preparing a modified composite catalyst for piperazine synthesis according to claim 5, wherein: In step S4, the mass ratio between the diphosphonic acid compound and the metal salt is 1:0.5-1.
5.
7. The method for preparing a modified composite catalyst for piperazine synthesis according to claim 6, wherein: In step S4, the concentration of NaOH in the NaOH aqueous solution is 1 mol / L, the volume fraction of the NaOH aqueous solution in deionized water is 4%-6%; and the mass ratio of the diphosphonic acid compound to the auxiliary agent is 1:2-2.
4.
8. The method for preparing a modified composite catalyst for piperazine synthesis according to claim 7, wherein: In step S5, the mass concentration of the metal phosphonate in the ethanol aqueous solution is 3-5 mg / mL; the mass concentration of the Cu / SiO2 composite material in the ethanol aqueous solution is 60-80 mg / mL.
9. The method for preparing a modified composite catalyst for piperazine synthesis according to claim 8, wherein: In step S5, the mass concentration of the sodium citrate in the ethanol aqueous solution is 2-4 mg / mL; the reaction temperature of the hydrothermal reaction is 160-180° C., and the hydrothermal reaction time is 12-18 hours.
10. A modified composite catalyst for piperazine synthesis prepared according to the preparation method according to any one of claims 1 to 9, characterized in that: The modified composite catalyst is used for catalyzing the synthesis of N-alkylpiperazine; the modified composite catalyst is used for catalyzing the synthesis of 1,4-dimethylpiperazine from N-methyldiethanolamine and monomethylamine.
Citation Information
Patent Citations
Catalyst for catalyzing saccharides to synthesize 5-hydroxymethyl furfural and method of catalyzing saccharides to synthesize the same
CN107163006A
Supported copper-based catalyst preparation method and applications of supported copper-based catalyst in synthesis of ethylene glycol
CN110694672A